Theoretical study on melting of phase change material by natural convection - Bingkun Huang (Elsevier, 2021)
Natural convection plays a crucial role in latent heat storage system. Determining how natural convection affects the melting of phase change material (PCM) will provide a better understanding of the melting process and give helpful advice on strengthening techniques. The research content of this paper is a mathematical model is established to explain the melting process of PCM affected by natural convection. The mathematical model of phase change melting process is given by introducing the natural convection and the temperature gradient. A coordination factor (Co) based on the mathematical model, which is an instantaneous quantity and proportional to the heat exchange rate and the intensity of natural convection, is introduced to explain the melting process. A square-shaped and shell-tube (concentric, eccentric) PCM heat storage unit were numerically analyzed in more detail. It is found that the Co factor is closely related to the melting rate. It will not promote the melting rate when Co less than 0 while it will promote the melting rate when Co higher than 0, and the higher the Co value, the faster the melting rate. This model gives a clear and quantitative explanation for the problem of melting interface movement affected by natural convection, as well as that increasing the heating temperature and changing only the shape of the heat storage unit can greatly enhance the heat storage rate in this study. The model also provides theoretical guidance for the study of the phase change heat storage enhancement.